Lycopene-rich diets modulate HDL functionality and associated inflammatory markers without affecting lipoprotein size and distribution in moderately overweight, disease-free, middle-aged adults: A randomized controlled trial - McEneny, Jane; Henry, Sarah-Louise; Woodside, Jayne; Moir, Susan; Rudd, Amelia; Vaughan, Nick; Thies, Frank (Frontiers in Nutrition, 2022)
Background: The consumption of lycopene-rich foods may lower CVD risk. Lycopene circulates in the blood bound to lipoproteins, including high density lipoproteins (HDL). Preliminary data from our group showed that increased consumption of tomato-based food or lycopene supplement in middle-aged subjects led to functional changes to HDL’s subfractions, HDL2 and HDL3. These changes were also associated with a decrease in serum amyloid A (SAA), potentially enhancing their antiatherogenic properties. Objective: We carried out a comprehensive randomized controlled intervention trial with healthy middle-aged volunteers to assess whether the consumption of tomato-based foods or lycopene supplement affects HDL functionality and associated inflammatory markers, as well as lipoprotein subfractions size and distribution. Design: Volunteers (225, aged 40–65 years) were randomly assigned into one of three dietary intervention groups and asked to consume a control diet (low in tomato-based foods, <10 mg lycopene/week), a lycopene-rich diet (224–350 mg lycopene/week) or the control diet with a lycopene supplement (70 mg lycopene/week). HDL2 and HDL3 were isolated by ultracentrifugation. Compliance was monitored by assessing lycopene concentration in serum. Systemic and HDL-associated inflammation was assessed by measuring SAA concentrations. HDL functionality was determined by monitoring paraoxonase-1 (PON-1), cholesteryl ester transfer protein (CETP) and lecithin cholesterol acyltransferase (LCAT) activities. Lipoprotein subfractions profile was assessed by nuclear magnetic resonance (NMR). Results: Lycopene in serum and HDL significantly increased following consumption of both the high tomato diet and lycopene supplement (p≤0.001 for both). Lycopene, either as a tomato-rich or a supplement, enhanced both serum- and HDL3-PON-1 activity (p≤0.001 and p=0.036, respectively), while significantly reducing HDL3-SAA-related inflammation (p=0.001). Lycopene supplement also significantly increased HDL3-LCAT activity (p=0.05), and reduced the activity of both HDL2- and HDL3-CETP activities (p=0.005 and p=0.002, respectively). These changes were not associated with changes in the subclasses distribution for all lipoprotein fractions or the size of lipoprotein subclasses. Conclusion: Our results showed that dietary lycopene can significantly enhance HDL functionality, without associated changes in particle size and distribution, by modulating the activity of HDL-associated enzymes. Concomitantly, dietary lycopene significantly decreased serum- and HDL3-associated SAA, confirming that SAA may represent a sensitive inflammatory biomarker to dietary change.